2014
DOI: 10.4110/in.2014.14.2.116
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Orphan Receptor NR4A1 is Involved in the Apoptotic Pathway Induced by LPS and Simvastatin in RAW 264.7 Macrophages

Abstract: Macrophage death plays a role in several physiological and inflammatory pathologies such as sepsis and arthritis. In our previous work, we showed that simvastatin triggers cell death in LPS-activated RAW 264.7 mouse macrophage cells through both caspase-dependent and independent apoptotic pathways. Here, we show that the nuclear orphan receptor NR4A1 is involved in a caspase-independent apoptotic process induced by LPS and simvastatin. Simvastatin-induced NR4A1 expression in RAW 264.7 macrophages and ectopic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…A study [41] showed that simvastatin decreased the TNF-alpha-induced apoptosis in endothelial progenitor cells by promoting the expression of silent information regulator type-1. Another study [42] showed that simvastatin triggers cell death in LPSactivated RAW 264.7 mouse macrophage cells through both caspase-dependent and independent apoptotic pathways. The nuclear orphan receptor NR4A1 expression and mitochondrial translocation of Bax are related to simvastatin-induced apoptosis in LPSactivated RAW 264.7 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…A study [41] showed that simvastatin decreased the TNF-alpha-induced apoptosis in endothelial progenitor cells by promoting the expression of silent information regulator type-1. Another study [42] showed that simvastatin triggers cell death in LPSactivated RAW 264.7 mouse macrophage cells through both caspase-dependent and independent apoptotic pathways. The nuclear orphan receptor NR4A1 expression and mitochondrial translocation of Bax are related to simvastatin-induced apoptosis in LPSactivated RAW 264.7 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…T-cells expressing chimeric antigen receptors (CAR) targeting human CD19 have exhibited impressive clinical efficacy against B cell cancers [151]. CAR T-cell have been less effective against solid tumors due to an increase in antigen stimulation and decrease effector function [152].…”
Section: Apoptosismentioning
confidence: 99%
“…4A shows, protein levels of inactive caspase-3 and -9 were decreased dose-dependently with administration of KTH-13-Me to C6 cells, while the levels of the active forms were highly increased. Since caspase-9 is involved in the mitochondrion-dependent intrinsic pathway in apoptosis, we also determined the protein level of Bcl-2, which prevents the release of cytochrome C from mitochondria ( Yang et al ., 1997 ; Kim et al ., 2014c ). As we expected, KTH-13-Me reduced the protein level of Bcl-2 in C6 cells, implying that the mitochondrial pro-apoptotic pathway could be stimulated by KTH-13-Me.…”
Section: Discussionmentioning
confidence: 99%